Мирный договор между Россией с одной стороны и Германией, Австро-Венгрией, Болгарией и Турцией с другой (Москва : Типография Московского совета рабочих и солдатских депутатов . Moskva: Tipografiya Moskovskogo soveta rabochih i soldatskih deputatov ., 1918)
Брестський мирний договір було підписано 3 березня 1918 р. у Брест-Литовську між Росією, з одного боку, та Німеччиною, Австро-Угорщиною, Болгарією, Туреччиною - з іншого боку. Встановлював припинення стану війни між Радянською республікою та країнами Четверного союзу.
Peace treaty between Russia on the one hand and Germany, Austria-Hungary, Bulgaria and Turkey on the other
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Military intelligence and security service; воєнна історія; Перша світова війна; The First World War; кінець війни; мирні переговори у Брест-Литовську; 3 березня 1918 року; відновлення дипломатичних та консульських зносин; відновлення державних договорів; турбота про реемігрантів; амністія; становище ворога, що потрапили у владу торгових суден і корабельних вантажів; Брестський мирний договір; митні правила; кордон Радянської Російської республіки з Німеччиною - мапа; історія Росії; military history; the end of the war; the peace negotiations in Brest-Litovsk; March 3, 1918; Russian-German additional contract to the peace treaty; Russia; Germany; Austria-Hungary; Bulgaria; Turkey; the reclamation of diplomatic and consular relations; recovery government contracts; recovery of private right; the fee for private law damages; care of reemigrants; amnesty; position of occurring in the power of the enemy merchant ships and cargo ship; duty with the Austrian and Hungarian goods; duties on Russian goods; Russian, Austro-Hungarian supplementary treaty to a peace treaty; Russian-Bulgarian supplementary treaty to the peace treaty; Brest peace treaty; customs rules; Russian-Turkish supplementary treaty to the peace treaty; the border of the Soviet Russian Republic with Germany (map); the history of Russia